Gabion wall used in road construction and flood protection embankment - Najeeb Utmani; Shiraz Ahmad; Riaz Ul Islam; Muhammad Abbas (Journal of Civil Engineering and Environmental Sciences - Peertechz Publications, 2019)
The scope of this paper is related to study of the gabion wall as retaining structure as well as load bearing member in hilly areas by considering various engineering factors such as structural stability, flexibility, aesthetics exposure and economic serviceability by following the design parameters such as overturning moment, sliding resistant and bearing pressure. Nowadays new construction methodologies as well design by various software's come into existent to make it easy the implementation of structure practically but due to adverse effects of climate changes, the concept of gabion wall retaining structure plays vital role for road construction in hilly areas as well as in flooding areas on the river banks. Its common in the recent days that structural member perform multiple duties for given project, but the concept of gabion retaining wall perform such type of needs. Gabion wall also control the erosion and scouring of land in flood protection embankment in the form of retaining structure, e.g. Gi wire retaining wall with various steps along with apron which provides launching and siltation after a period of time or high flooding. Such type of gabion retaining wall is used in KP province of Pakistan after high flood disaster occurred in 2010 on River Kabul District Nowshera. Objective of the study: The main objective of gabion walls is to control land sliding on road sides, erosion and scouring on the rivers banks during flood and high velocity river streams and prevent the water logged areas from further damaging. They also support the moment of the soil and rock laterally in hilly areas by providing the function of breast walls. Our main goal is to enlighten the gabion wall as retaining structure as well load bearing member by determining its dual behaves in order to provide the strength, efficiency and structural stability by decreasing the total estimating cost while retaining the aesthetics needs and following the actual design and routine supervision. The paper also focuses on determining the conditions and implementing of gabions walls in bridge abutments and culverts and pier for elevated flyovers which are acting as breast walls by evaluating the parameters of overturning movement, resisting movement, sliding resistant and load bearing force.